Epistemology of Religious Knowledge in Nineteenth-Century Pesantren as a Historical Source: A Philosophy of Science Perspective - Muhammad Abdul Kharis; Nurul Iffatiz Zahro; Tety Juwariyah (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This paper examines the epistemology of Islamic boarding school (pesantren) religious knowledge in 19th-century Java and positions it as a historical source in the study of Indonesian Islamic history. Historiography has traditionally positioned Islamic boarding schools as socio-religious objects, while their scholarly traditions have rarely been read as producers of historical knowledge. Through an intellectual history and philosophy of science approach, this study attempts to dissect the epistemic tradition of Islamic boarding schools, encompassing the sanad-based system of knowledge transmission, the scholarly authority of kyai (Islamic scholars), the use of kitab kuning, and learning practices such as talaqqi (religious teachings) and bandongan (religious recitation). The results demonstrate that Islamic boarding school religious knowledge has a well-established epistemological foundation, internal validation mechanisms, and historical continuity that can be scientifically justified. In the Javanese context, specifically in the 19th century, this epistemic tradition not only functioned as a medium for transmitting religious teachings but also recorded the traces of intellectuals, networks of ulama (Islamic scholars), and scholarly responses to the dynamics of colonialism. Therefore, the epistemology of Islamic boarding school religious knowledge can be positioned as a legitimate historical source. This paper expands the conception of history and offers a critique of the limitations of the positivistic historiographic approach in writing the history of Islam in Indonesia.